Anatomical and Functional Outcomes After Silicone Oil Tamponade in Patients With Complex Retinal Detachment - Hussain, Sajjad; Rao, Rashad Qamar (Biological and Clinical Sciences Research Journal, 2025)
Complex retinal detachment (RD), including tractional retinal detachment (TRD) and traction-rhegmatogenous retinal detachment (TRRD), poses significant challenges in vitreoretinal surgery. Pars plana vitrectomy (PPV) with silicone oil (SO) tamponade is a widely used technique to achieve anatomical success; however, visual outcomes and postoperative complications remain variable. This study evaluates anatomical and functional outcomes after PPV with SO tamponade in patients with complex RD in Pakistan. Objective: To assess the anatomical success rate, functional visual outcomes, and postoperative complications associated with PPV with SO tamponade in patients with complex RD at Nishtar Hospital, Multan. Methods: An observational study was conducted on 37 patients (40 eyes) who underwent PPV with SO tamponade for complex RD. Preoperative complexity scoring (CS: 4–8) was assigned based on macular involvement, vitreoretinal traction, and prior pan-retinal photocoagulation (PRP). Primary outcome measures included anatomical success (complete retinal reattachment) and postoperative visual acuity (VA). Secondary outcomes included complication rates and timing of silicone oil removal (SOR). Data were analyzed using SPSS version 26, applying paired t-tests and chi-square tests for statistical comparisons (p ≤ 0.05 significant).Results: The primary anatomical success rate was 85%, with a significantly higher success rate in macula-sparing TRD cases (91.7%) compared to macula-involving TRD (72.2%) (p < 0.05). Patients with preoperative complexity scores ≤5 had better postoperative VA, with 50% achieving VA ≥ 20/400 postoperatively. Preoperative PRP was associated with a 90% anatomical success rate, compared to 66.7% in patients without PRP. Postoperative complications included cataract formation (46%), retinal fibrosis (33%), and recurrent RD (15%). SOR was performed in 27.5% of eyes, with early SOR (≤3 months) leading to better visual recovery. Conclusion: The average complexity score was high in this series. SO tamponade for diabetic TRDs is not without complications, but it may be beneficial in stabilizing vision in eyes with otherwise poor prognosis.PPV with SO tamponade is highly effective for managing complex RD in Pakistani patients, with a high anatomical success rate and moderate functional improvement. Macula involvement, preoperative complexity scores, and PRP status significantly influenced surgical outcomes. The findings highlight the need for structured PRP protocols and optimal timing of SOR to improve visual prognosis. Future studies should focus on long-term follow-up and the impact of hybrid tamponade strategies on functional vision outcomes.